Perilaku Masyarakat Adat Boti dalam Mempertahakan Kelestarian Budaya pada Desa Adat Boti, Kabupaten Timor Tengah Selatan - Meiliana Afliana Babu (CV. Ulil Albab Corp, 2023)
Culture is local wisdom that has important value in people's lives, especially in Boti village, South Central Timor Regency. The community not only uses culture as a role model, but also attracts tourists, both foreign tourists and domestic tourists. Most tourists who visit are to see firsthand parts of the existing culture such as customs, rituals, traditional houses and clothing as well as traditional communities. Many follow-up visits have caused cultural shifts, but have further strengthened indigenous communities to preserve their culture from generation to generation. Therefore, from this research, researchers want to learn more deeply about how the communication behavior of indigenous peoples maintains and preserves culture in Boti village. This research was conducted using qualitative methodology with an ethnographic approach involving traditional leaders, tribal leaders and young people. The research results obtained in this study show that there is a pattern of communication behavior in indigenous communities which is depicted in the star communication pattern. Referring to this model, it is clear that every person who communicates really reflects the extent to which indigenous peoples still maintain the preservation of their traditions. This can be seen in verbal and non-verbal communication as well as the means of communication used.